2010
DOI: 10.1021/ac1011798
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Selenium Metabolic Pathway in Yeast by Liquid Chromatography−Orbitrap Mass Spectrometry

Abstract: A high resolution mass spectrometric detection method is described for the identification of key metabolites in the selenium pathway in selenium enriched yeast. Iodoacetic acid (IAA) was used as the derivatizing reagent to stabilize the selenols. Oxidized forms of Selenocysteine (Se-Cys), selenohomocystine (Se-HCys), selenoglutathione (Se-GSH), seleno-γ-glutamyl-cysteine (Se-Glu-Cys), N-(2,3-dihydroxy-1-oxopropyl)-Selenocysteine (SELM-1). Selenols were also derivatized with a mercury tag, p-hydroxymercurybe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 68 publications
0
46
0
Order By: Relevance
“…Indeed, the inorganic form of selenium, selenite, has been reported to be involved in induction of DNA damage (29). A sensitive method has recently been established to identify selenium compounds from yeast cells treated with SeMet, using Orbitrap mass spectrometry (30). However, metabolic changes in SeMet-treated cells were not clearly addressed in this report.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, the inorganic form of selenium, selenite, has been reported to be involved in induction of DNA damage (29). A sensitive method has recently been established to identify selenium compounds from yeast cells treated with SeMet, using Orbitrap mass spectrometry (30). However, metabolic changes in SeMet-treated cells were not clearly addressed in this report.…”
Section: Discussionmentioning
confidence: 89%
“…Superoxide production was observed in SeMet-treated yeast cells and deletion of SOD1, the gene coding for superoxide dismutase, was shown to increase SeMet toxicity (113). In addition, metabolomic studies in yeast demonstrated that SeMet addition induced a redox imbalance (149,150). How exposure to SeMet generates oxidative stress remains to be established.…”
Section: Selenomethionine Toxicitymentioning
confidence: 99%
“…Selenide is also the intermediate for the formation of selenocysteine, from which selenomethionine can then be formed in organisms with a functional transsulfuration pathway. Several metabolomics studies 282930 have shown that a plethora of additional organoselenium compounds accumulate in yeast cells supplemented with selenate, selenite or selenomethionine, in addition to demonstrating that selenocysteine can also be formed from selenomethionine.…”
Section: Se Compounds In Naturementioning
confidence: 99%